Sero-prevalence of toxoplasmosis in sheep and goats in El-Gadarif state - Atail, Hamadnalla Babiker; Ibrahaem, Hatim Hamad; Shuaib, Yassir Adam; Mohamed, Abdelgadir Khalid; Suliman, Siham Elias; Idris, Salah Hassan; Abdalla, Mohamed Abdelsalam (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This cross-sectional study was conducted from July to November 2015 to estimate the prevalence of anti-toxopalsma antibodies in sheep and goats in El-Gadarif state. Material and methods: A total of 400 serum samples comprising of 200 sheep and 200 goats were collected and tested by Toxo-latex agglutination test and indirect enzyme linked immunosorbent assay (iELISA). Results: The overall sero-prevalence was 52.0% (n=208/400) using Toxo-latex agglutination test and 45.7%(n=42/92) and 27.2%(n=25/92) using iELISA in sheep and goats, respectively. Furthermore, the sero-prevalences among the two investigated species and the two age groups were statistically similar but were different between localities, breeds and sexes. In the univariate analysis, species (P=0.028) and locality (P=0.001) were associated with Toxo-latex agglutination test positive status. Additionally, species (sheep) and locality (Al-Fao, Al-Hawatah, and West El-Gadarif) had increased odds of being Toxo-latex agglutination test positive in the multivariate analysis. Conclusion: It can be concluded that the prevalence of anti-toxopalsma antibodies is relatively high and there was no between-species variation in sero-positivity. These findings warrant further investigations to estimate the burden of the disease and the likelihood of zoonotic transmission. http://doi.org/10.5455/javar.2017.d205 XML PubReader